Health information-seeking behaviours among pregnant teenagers in Ejisu-Juaben Municipality, Ghana. (October 2016) - Owusu-Addo, Sally B.; Owusu-Addo, Ebenezer; Morhe, Emmanuel S.K.
Abstract: Objective: to examine health information-seeking behaviours among pregnant teenagers. Design: qualitative design using semi-structured interviews and focus groups. The study followed the Consolidated Criteria for Reporting Qualitative Studies (COREQ). Settings/Participants: antenatal clinic at Ejisu Government hospital, Ghana. Twenty eight pregnant teenagers aged 15–19 and one midwife participated in the study. Method: the participants were interviewed in person at the antenatal clinic. The individual interviews and focus groups were digitally recorded, transcribed, and then analysed using thematic framework analysis. Findings: three themes emerged from the analysis of the transcripts: information needs, sources of information and barriers to information seeking. Findings indicate unmet information needs among pregnant teenagers including proper understanding of pregnancy stages, infant feeding practices, nutrition, labour and birth and postnatal care. Pregnant teenagers largely relied on traditional sources for information on pregnancy as compared to official sources such as midwives, nurses or doctors. Conclusion/Implications for practice: given that traditional sources, such as family and neighbours were the predominant sources of information, to effectively and comprehensively address the information needs of pregnant teenagers, interventions should target both the expecting teenagers and the family and/or the community at large. The findings further point to a need for a shift in maternal health care policy through the establishment of adolescent only antenatal care day to effectively meet the heath information needs of pregnant teenagers. Highlights: Unmet information needs included proper understanding of the stages of pregnancy, infant feeding practices, nutrition in pregnancy and postnatal care. Pregnant teenagers largely relied on traditional sources for information on pregnancy related issues as compared to official sources such as midwives, nurses or doctors. Personal and structural issues within the clinic setting served as barriers to meeting the information needs of the pregnant teenagers. Health promotion interventions aiming at addressing information needs of pregnant teenagers should target both the pregnant teenagers and the family and/or the community.